Acute Kidney Injury in Critically Ill Patients: A Prospective Randomized Study of Tidal Peritoneal Dialysis Versus Continuous Renal Replacement Therapy. Issue 4 (25th March 2018) - Al‐Hwiesh, Abdullah; Abdul‐Rahman, Ibrahiem; Finkelstein, Fredric; Divino‐Filho, Jose; Qutub, Hatem; Al‐Audah, Nadia; Abdelrahman, Abdalla; El‐Fakhrany, Nazeeh; Nasr El‐Din, Mohammed; El‐Salamony, Tamer; Noor, Abdulsalam; Al‐Shahrani, Mohammed; et al.
Abstract: Few studies have discussed the role of peritoneal dialysis (PD) in managing acute kidney injury (AKI) in critically ill patients. The present study compares the outcome of AKI in intensive care unit (ICU) patients randomized to treatment with tidal PD (TPD) or continuous venovenous hemodiafiltration (CVVHDF). One hundred and twenty‐five ICU patients with AKI were randomly allotted to CVVHDF, (Group A, N = 62) or TPD, (group B, N = 63). Cause and severity of renal injury were assessed at the time of initiating dialysis. The primary outcome was hospital mortality at 28 days, and secondary outcomes were time to recovery of renal function, duration of stay in the ICU, metabolic and fluid control, and improvement of sensorial and hemodynamic parameters. No statistically significant differences were observed between groups in regard to patients' characteristics. The survival at 28 days was significantly better in the patients treated with TPD when compared to CVVHDF (69.8% vs. 46.8%, P  < 0.01). Infectious complications were significantly less ( P  < 0.01) in the TPD group (9.5%) when compared to the CVVHDF group (17.7%). Recovery of kidney function (60.3% vs. 35.5%), median time to resolution of AKI and the median duration of ICU stay of 9 days (7–11) vs. 19 days (13–20) were all in favor of TPD ( P  < 0.01). This study suggests that there are better outcomes with TPD compared to CRRT in the treatment of critically ill patients with AKI.